"Dysphagia lusoria" – Right subclavian retroesophageal artery causing intermitent esophageal compression and eventual dysphagia – A case report and literature review. (2015) - de Araújo, Guilherme; Junqueira Bizzi, Jorge Wladimir; Muller, Jader; Cavazzola, Leandro Totti
Highlights: Case report of a right subclavian retroesophageal artery (RSRA) found occasionaly on a chest CT. The malformation caused intermittent dysphagia. Patient presented with long history of upper digestive symptoms and gastroesophageal reflux disease. Abstract: We report a case of an uncommon anatomical anomaly in which a right subclavian retroesophageal artery (RSRA) was discovered during a routine chest CT scan in a patient with intermittent upper digestive symptoms (occasional dysphagia for solids, the so called "globus hystericus"). Subclavian arteries vary in their origin, course or length. RSRA is a relatively common embryological anomaly of the aortic arch. In this case we report a single carotid trunk. This variation is due to interruption of the fourth right aortic arch between the origins to the common carotid artery and subclavian artery, while the fourth left arch is intact. The regression of the proximal portion of the right subclavian artery occurs and the retroesophageal aortic arch persists, rarely leading to symptoms, as were present in this case.